The 1970s and scenography in Maranhão, a description of the main performances (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2022)
In this study I briefly describe the scenography of the main spectacles staged in São Luís, Maranhão, from 1971 to 1978 by the following groups: Teatro de Férias do Maranhão, Armação de São Luís, Teatro Experimental do Maranhão, Mutirão and LABORARTE. The choice of these groups and the historical period is based on three fundamental aspects: the first was my participation in all of them (as playwright, actor and/or director); the second is the fact that they were performances that had a more elaborate scenography, where one can glimpse, even if superficially, the ideas of Appia, Craig and Meierhold; the third is that a search in any of the city's dailies does not find a critique of their scenographies.
Keywords: theater; scenography; Maranhão; 1970s